Evaluasi efek pre-treatment ultrasonik pada proses hidrolisis enzimatis ampas tahu - Farlina Hapsari; Imam Prasetyo; Wiratni Budhijanto (Jurnal Rekayasa Proses, 2015)
Utilization of biomass as alternative energy source is one of the attempts to reduce the dependence on petroleum based energy which is currently still used as the primary energy source. Tofu solid waste is one of the potential biomass sources that have not been fully utilized. Tofu solid waste was mostly comprised of complex molecular structures composed of cellulose, hemicellulose and lignin. Various techniques of pretreatments have been studied to change the physical structure and chemical properties of the biomass to improve its digestibility in enzymatic hydrolysis process. This research studied the effect of ultrasonic pretreatment on tofu solid waste prior to the enzymatic hydrolysis to maximize the conversion of the cellulose into glucose. Ultrasonic pretreatment was conducted by using a water bath equipped with ultrasonic equipment (sonicator) run at the wave frequency of 20 kHz and power of 5 kW. Ultrasonic pretreatment with variations of time (10, 20 and 30 minutes) and temperatures (60 °C, 80 °C, 100 °C) were carried out. Following the pretreatment, hydrolysis tests were conducted on pretreated samples using cellulase enzymes in 100 ml batch reactor at 45 oC and pH 5. Samples were taken every 1 hour for 6 hours of the reaction and glucose concentration in every sample was measured. The highest cellulosic conversion in enzymatic hydrolysis was obtained on the biomass which was pretreated with ultrasonic for 20 minutes.